Sedentary behavior among adults: The role of community belonging - Scott Anderson; Cheryl L. Currie; Jennifer L. Copeland (Preventive Medicine Reports, 2016)
Sedentary behavior is a modifiable determinant of health. Little is known about the ways in which contextual factors may influence this behavior. The objectives of this study were to: (1) examine the association between community belonging and adult sedentary behavior during leisure; (2) determine if this association was explained by perceived health. Data were derived from the 2010 Canadian Community Health Survey (N = 11,494 adults). Multinomial regression models and 99% confidence intervals were used to examine associations between sense of community belonging and sedentary behavior, adjusting for sociodemographic variables and perceived health. On average, adults were sedentary for 20–24 h per week during leisure. More than a third of the sample reported low sedentary behavior (≤19 h a week). In a fully adjusted model participants who were female, in middle adulthood, married, and/or living in higher income households were less sedentary during leisure. Adults with a strong sense of community belonging were also significantly less sedentary during leisure; this association remained significant after adjustment for perceived mental and overall health. Most efforts to address sedentary behavior have focused on individual-level interventions. The present finding highlights the role that larger contextual factors may play in sedentary behavior. Sense of community belonging is a contextual determinant of health that may serve as a useful target for interventions designed to reduce adult sedentary behavior during leisure. Keywords: Sedentary behavior, Contextual factors, Community belonging, Perceived health